PUSHOVER ANALYSIS OF REINFORCED CONCRETE BUILDING WITH VERTICAL SHEAR LINK STEEL BRACES (Malaysian Journal of Civil Engineering, 2018)
In recent decades, steel cross bracing has been used as a conventional method to retrofit concrete buildings. Most of the cases utilized concentric steel braces system. However, studies concerning the behavior of RC frames with eccentricity steel bracing are quite limited. In this research, three types of structures incorporating special moment frames, RC structure with invert V braces and RC structures with vertical link beams with different stories were modeled through SAP 2000 and analyzed by considering nonlinear static analysis (pushover). Results revealed that invert Y steel braces (vertical shear links) system is an alternative way to construct a ductile structure with great lateral stiffness. It was also found that the axial force in braces is controlled by the behavior of the vertical link beam.